2021
DOI: 10.3390/nano11102597
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Enhanced Second Harmonic Generation from ZnO Nanofilms on Vertical Au Nanorod Arrays

Abstract: Vertically aligned gold nanorod arrays have attracted much attention for their fascinating optical properties. Different from longitudinal surface plasmon wavelength (LSPW) and edge-to-edge spacing of gold nanorods, the role of gold nanorod diameter in plasmonic enhancement ability of vertical gold nanorod arrays has rarely been explored. In this work, we selected gold nanorods with similar LSPW but two different diameters (22 and 41 nm), the optical properties of which are dominated by absorption and scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Third-order optical nonlinearities can be controlled by irradiance, polarization, and concentration of different sizes and morphologies of crystals in ZnO nanostructures [45]. In addition, it has been reported that ZnO nanocrystals, nanofilms, nanowires [46], and bulk structures can be used as nonlinear media to obtain higher-frequency conversion efficiencies from nonlinear effects [47,48]. Also, various ZnO-based nanohybrids have been examined for the enhancement of their nonlinear optical interactions [49][50][51][52][53][54][55][56].…”
Section: Nanosecond Twm Studiesmentioning
confidence: 99%
“…Third-order optical nonlinearities can be controlled by irradiance, polarization, and concentration of different sizes and morphologies of crystals in ZnO nanostructures [45]. In addition, it has been reported that ZnO nanocrystals, nanofilms, nanowires [46], and bulk structures can be used as nonlinear media to obtain higher-frequency conversion efficiencies from nonlinear effects [47,48]. Also, various ZnO-based nanohybrids have been examined for the enhancement of their nonlinear optical interactions [49][50][51][52][53][54][55][56].…”
Section: Nanosecond Twm Studiesmentioning
confidence: 99%
“…This Special Issue aims to provide an overview of the current advances in nanophotonic and optical nanomaterials in China and to prompt new interest in this field. The collected eight articles [1][2][3][4][5][6][7][8] highlight the latest progress in nanophotonics and materials science, including developments of novel nanomaterials and ingenious nanoscale designs. These contributions may unveil new opportunities to control light, provide effective ways to optimize targeted performances, and have important implications for novel photonic devices operating beyond the diffraction limit.…”
mentioning
confidence: 99%
“…Notably, nanomaterial structures play important roles in the optimization of device performances. In this context, vertically aligned Au nanorod arrays with two different diameters were prepared by Ma et al based on the evaporation self-assembly method, which was used to realize a strong plasmon enhancement on the second harmonic generation [3]. Yu et al proposed a novel method to prepare high dispersibility silver nano-ink-filled particles, in which the addition of filling particles could effectively improve its electrical conductivity without significantly changing the metal solid content in the ink [4].…”
mentioning
confidence: 99%